Homomorphism between Rings - S., Vinod; G. S., Biju; N. S., Minikumari (Communications in Mathematics and Applications, 2020)
In this paper, using elementary algebra and analysis, we characterize and compute all ring homomorphism from \(Z^n\) to \(Z^m\) and from \(Q^n\) to \(Q^m\). Also, we characterize and compute all continuous ring homomorphism from \(R^n\) to \(R\).